Protective effects of benfotiamine on cyfluthrin-induced testicular damage and sperm characteristics during the prepubertal period - Parlak, Gozde; Colakoglu, Neriman (Springer, 2024)
Cyfluthrin, a widely used synthetic pyrethroid insecticide, poses potential risks to both human health and the environment due to its extensive application in residential, agricultural, and outdoor settings. Conversely, benfotiamine, a fat-soluble derivative of vitamin B1, offers versatile therapeutic potential. This experimental study aimed to investigate the impact of cyfluthrin exposure during the prepubertal period on sperm characteristics and testicular tissue integrity in male rats, as well as to assess the protective effects of benfotiamine. A total of 32 4-week-old Wistar albino male rats were divided into four groups. Group I received daily oral gavage of 1 ml/kg/day of olive oil (control). Group II was administered cyfluthrin (54 mg/kg/day) dissolved in 1 ml of olive oil. Group III received both cyfluthrin (54 mg/kg/day) and benfotiamine (100 mg/kg/day) in olive oil. Group IV was given benfotiamine (100 mg/kg/day) in olive oil. After 5 weeks of treatment, the rats underwent evaluations for sperm motility, epididymal sperm density, and abnormal sperm rates. Additionally, their testicular tissues were examined histologically and immunohistochemically. This study underscores the potential hazards of cyfluthrin exposure on male reproductive health and highlights the protective role of benfotiamine in mitigating these effects. It emphasizes the importance of careful pesticide usage and dosage considerations to prevent potential public health issues, including infertility, associated with long-term exposure to pesticides like cyfluthrin.
Keywords: Cyfluthrin; Benfotiamine; HSP 70; Testis; Sperm